Gordon in charge - Newton, Jill, 1964- (New York : Bloomsbury Children$1 (Bs Books,s, 2003)
Gordon the Goat is in charge of the farmyard until Gordon the Goose arrives to challenge him and, after a series of competitions gets them in trouble, they learn who is the real boss.
Keywords: Bossiness -- Fiction; Goats -- Fiction; Geese -- Fiction; Domestic animals -- Fiction; Humorous stories